Aggregated coefficients of IT projects labor resources - A. A. Kotkovets; S. A. Pottosina; T. G. Pinchuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The purpose of this article is to reduce the cost and time for the formation of a project team, as well as improve the quality of selected teams, by automating the process of calculating the labor resources of project teams. The objectives of the article are to study and analyze theoretical works on project teams formation and the construction of aggregated coefficients of a project and an employee for IT projects labor resources calculation. The article reveals the basic concepts and mechanisms of project management and human resources of an IT organization; the process of a project team forming and its structure, which is made up of the customer's team and the executor's team, is considered. A set of key indicators of a project and an employee is highlighted, which are necessary components for introducing the concept of an aggregated coefficient. The description of the calculation of the aggregate coefficient of the project (Iп), the aggregate coefficient of the employee (Ic), as well as the project aggregated coefficient of the employee (Ic п ) is provided, since the aggregated indicators of the project and the employee are independent in relation to each other, and to solve the tasks we need a coefficient that describes usefulness and efficiency of attracting a specific employee for a specific project. The theoretical significance of the work lies in the fact that it describes the process of project teams building in details, proposes aggregated coefficients of projects and employees, which make it possible to assess and select labor resources for project teams. The obtained theoretical results can be used to assess the role of each employee on a separate project and in the company as a whole, to calculate the labor resources of IT projects, as well as by the search and project planning department when choosing the scope and nature of work for the period under consideration.